2016
DOI: 10.1177/0888406416654212
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Teachers’ Perceptions of Challenging Behavior

Abstract: Challenging behavior can have adverse effects on both students and teachers, and preservice teachers often report feeling ill prepared to manage this behavior. The purpose of this study was to examine (a) preservice teacher perceptions of student and teacher behavior during scenarios of challenging behavior, (b) alternative solutions or strategies in examining the teacher’s role in the scenarios, (c) perceptions of challenging behaviors that may present the greatest difficulty in their future positions, and (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…According to Baker’s study (2005), teachers’ perceived self-efficacy in managing challenging situations can predict their willingness and ability to manage those situations [23]. A teacher’s behavior and interaction with their pupils influence the pupils’ behavior [32], and a teacher’s ability to choose the right ways to act and intervene can prevent the escalation of problematic situations [27]. For example, an argument about seating may be avoided by asking the pupil where they want to sit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Baker’s study (2005), teachers’ perceived self-efficacy in managing challenging situations can predict their willingness and ability to manage those situations [23]. A teacher’s behavior and interaction with their pupils influence the pupils’ behavior [32], and a teacher’s ability to choose the right ways to act and intervene can prevent the escalation of problematic situations [27]. For example, an argument about seating may be avoided by asking the pupil where they want to sit.…”
Section: Discussionmentioning
confidence: 99%
“…Managing pupils’ behavior at school is a challenge for teachers [23,24], yet teacher training often does not adequately prepare future teachers for managing the behavioral needs of diverse learners [25,26]. Teachers may not be capable of choosing the right ways of responding to pupils’ behavior, which may escalate the problem [27]. Teachers’ low self-efficacy in classroom management is associated with challenging behavior in the class as well as with the emotional exhaustion of teachers [28].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of classroom behaviour management, teachers often report low confidence and feelings of being ill prepared in classroom behaviour management (Butler & Monda-Amaya, 2016;Hepburn & Beamish, 2019;Reinke, Stormont, Herman, Puri, & Goel, 2011;Skiba, Ormiston, Martinez, & Cummings, 2016). Even when teachers have the knowledge of evidence-based classroom management strategies, they may not implement the practices consistently (Jeffrey, McCurdy, Ewing, & Polis, 2009;Reinke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, teachers who are skillful with classroom management are able to handle students' behavior issues well. Many studies showed teachers who demonstrate a good knowledge and understanding of behavior management could handle this situation confidently and positively (Butler & Monda-Amaya 2016;Ahmad & Hanifah, 2015). A review of the literature agreed on knowledge as a basic component that needs to empower to make sure teachers are competent enough dealing with challenging behavior (Zulkifli & Mohamed, 2019;Wei & Yasin, 2017;Bari, Yasin & Hamzah, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite all the research spotlight focuses on teacher's knowledge, perceptions, attitude and practice towards behavior management, only a few studies investigated the readiness of pre-service teachers in dealing with behavior issues of their students (Butler & Monda-Amaya 2016;Reupert & Woodcook, 2010). Are they well prepared to deal with this situation?…”
Section: Introductionmentioning
confidence: 99%